Genetic and flower volatile diversity in two natural populations of Hyssopus officinalis L. in Bulgaria. Issue 1 (1st January 2020) - Zagorcheva, Tzvetelina; Rusanov, Krasimir; Rusanova, Mila; Aneva, Ina; Stancheva, Ira; Atanassov, Ivan
Abstract: The genetic and flower volatile diversity of 59 plants from two natural populations of Hyssopus officinalis L. situated 73 km away from each other in typical growing regions for this species in Bulgaria were analysed. Analysis with 10 sequence related amplified polymorphism (SRAP) primer combinations scored a total of 1045 peaks of which 88.7% were polymorphic. Principal Coordinate Analysis (PCoA) and unweighted pair group method with arithmetic mean (UPGMA) clustering revealed clear grouping of samples based on their population origin. However, analysis of the genetic differentiation revealed that the two populations (Godech and Izvor) are genetically similar as shown by the low Fst and Gst values as well as by the low Nei's genetic distance and high gene flow (Nm). Gas chromatography–mass spectrometry (GC-MS) analysis of flower extracts from the same individual plants that were used in the genetic diversity analysis identified 32 compounds. Principal Component Analysis (PCA) based on compound abundances revealed two major clusters of samples which did not correspond to their population origin. In depth analysis of the compound abundances showed large variation between the two identified clusters including complete presence/absence of major compounds and the existence of two distinct chemotypes corresponding to the identified clusters. Our results indicate that future efforts towards development of genetic resource collections as well as transition towards field cultivation of this species in Bulgaria should take into account the presence of the two identified chemotypes in natural populations and the factors (both genetic and epigenetic) which determine their existence.